Strategi Orientasi pada Industri Manufaktur yang Ada di Kabupaten Banyuwangi - Annisa Aulia Lestari; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The manufacturing industry sector has an important role in supporting economic growth in Banyuwangi Regency. The increase in industrial activities contributes to employment opportunities, regional income growth, and the expansion of economic activities in urban and rural areas. Each region in Banyuwangi has different industrial development characteristics influenced by transportation accessibility, infrastructure availability, land conditions, and proximity to trade and distribution centers. This study aims to analyze the orientation strategy of the manufacturing industry in Banyuwangi Regency using a spatial approach based on Geographic Information Systems (GIS). The research method used is descriptive quantitative with spatial analysis. The results show that manufacturing industries tend to develop in areas with good transportation access and adequate infrastructure support. Industrial concentration is also dominant in regions close to economic activity centers and distribution routes. The development of manufacturing industries has positive impacts on regional economic growth, employment opportunities, and community income. However, industrial concentration in certain areas may create regional development inequality. Therefore, sustainable industrial planning is required to support balanced regional development in Banyuwangi Regency.